2012
DOI: 10.1002/etc.1729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a glucocorticoid receptor agonist, dexamethasone, on fathead minnow reproduction, growth, and development

Abstract: Synthetic glucocorticoids are pharmaceutical compounds prescribed in human and veterinary medicine as anti-inflammatory agents and have the potential to contaminate natural watersheds via inputs from wastewater treatment facilities and confined animal-feeding operations. Despite this, few studies have examined the effects of this class of chemicals on aquatic vertebrates. To generate data to assess potential risk to the aquatic environment, we used fathead minnow 21-d reproduction and 29-d embryo-larvae assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 45 publications
2
71
3
Order By: Relevance
“…Therefore, the seasonal variation in detection frequency/concentration of GCs should be monitored to reveal the controlling factors and potential adverse effects on the aquatic biota. In the present study, all the detected GC levels were less than reported Lowest Observable Adverse Effect Concentration (LOAEC) (Kugathas et al 2013;Kugathas and Sumpter 2011;LaLone et al 2012). However, further research on the toxicity of GCs in the aquatic environment is required.…”
Section: Inter-plant Variation In Gc Levels In Stp Effluentcontrasting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the seasonal variation in detection frequency/concentration of GCs should be monitored to reveal the controlling factors and potential adverse effects on the aquatic biota. In the present study, all the detected GC levels were less than reported Lowest Observable Adverse Effect Concentration (LOAEC) (Kugathas et al 2013;Kugathas and Sumpter 2011;LaLone et al 2012). However, further research on the toxicity of GCs in the aquatic environment is required.…”
Section: Inter-plant Variation In Gc Levels In Stp Effluentcontrasting
confidence: 65%
“…However, some medicines may be discharged to the aquatic environment due to their low removal or deconjugation during sewage treatment processes. The adverse effect of dexamethasone on reproduction of fathead minnow was reported at a high exposure level (500 μg/L) (LaLone et al 2012). In addition, relatively low levels of prednisolone and beclomethasone exposures resulted in increase in plasma glucose and decrease in peripheral blood leucocytes (Kugathas and Sumpter 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Our results in vitro reveal that glucocorticoid signaling on clock genes is directly targeting the liver, and in fact glucocorticoid receptors have been reported in the liver of some teleosts (Aluru and Vijayan 2007;LaLone et al 2012;Teles et al 2013). In this study we have analyzed the effects of glucocorticoids not only on per genes that are the most studied genes related to these hormones (Balsalobre et al 2000;Fukuoka et al 2005;Yamamoto et al 2005), but also on the genes from the positive loop of the molecular machinery of the clock.…”
Section: Discussionmentioning
confidence: 92%
“…Cortisol also inhibits pubertal development in Cyprinus carpio and that this inhibition is present at all levels of the HPG axis (Goos and Consten, 2002). Furthermore, detrimental effects on reproduction, growth, and development were observed with exposure of fathead minnow (Pimephales promelas) during 21 days to a high concentration (500 μg/L) of dexamethasone (LaLone et al, 2012).…”
Section: Discussionmentioning
confidence: 97%